2022
DOI: 10.3390/nu14081558
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation Favours NOX2-Mediated Muscle Damage in Elite Athletes: The Role of Cocoa-Derived Polyphenols

Abstract: Mechanisms of exercise-induced muscle injury with etiopathogenesis and its consequences have been described; however, the impact of different intensities of exercise on the mechanisms of muscular injury development is not well understood. The aim of this study was to exploit the relationship between platelet activation, oxidative stress and muscular injuries induced by physical exercise in elite football players compared to amateur athletes. Oxidant/antioxidant status, platelet activation and markers of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A previous study demonstrated that polyphenol-rich nutrient supplementation with dark chocolate positively modulated redox status and reduced exercise-induced muscular injury biomarkers in elite football athletes [ 30 ]. Moreover, in vitro studies support the positive effect of cocoa-derived polyphenols, as skeletal muscle myoblast cell lines treated with polyphenol extracts displayed decreased oxidative stress and muscle injury biomarker levels [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that polyphenol-rich nutrient supplementation with dark chocolate positively modulated redox status and reduced exercise-induced muscular injury biomarkers in elite football athletes [ 30 ]. Moreover, in vitro studies support the positive effect of cocoa-derived polyphenols, as skeletal muscle myoblast cell lines treated with polyphenol extracts displayed decreased oxidative stress and muscle injury biomarker levels [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes were coincident with increased levels of biomarkers of muscle injury such as LDH, CK, and myoglobin [ 30 ]. Moreover, elite football players compared to amateurs displayed increased concentrations of dopamine, which plays a key role in favoring platelet activation and in promoting NOX2-mediated oxidative stress, ultimately favoring muscle injury [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent paper by D’Amico et al (2022) studied the relationship between blood platelet activation, oxidative stress and muscular injuries stimulated by physical exercise, as well as the role of cocoa-derived phenolic compounds, in elite athletes. Their results suggest that the cocoa-derived phenolic compounds: catechin and epicatechin significantly reduce oxidative stress and muscle injury in supernatants of human skeletal muscle myoblast cell cultures treated with plasma.…”
Section: Cardioprotective Mechanisms Of Cocoa Phenolic Compoundsmentioning
confidence: 99%
“…The oxidative burst is mediated by NADPH oxidase, which produces O 2 - and H 2 O 2 [ 77 ], and these products achieve their cytotoxic effects due to reactions with other antimicrobial systems to generate ROS [ 67 , 78 ]. In skeletal muscle cells in culture, two primary NADPH oxidase isoforms (NOX2 and NOX4) [ 79 ] were found to be the main sources of ROS [ 80 , 81 ]. Thus, the role of NADPH oxidase-derived ROS is important in pathogen-mediated and sterile inflammation (i.e., without pathogen involvement).…”
Section: Properties Of Polyphenol-based Dietary Supplementsmentioning
confidence: 99%